Análise crítica de gênero: significados ideacionais em artigos acadêmicos audiovisuais de protocolo de pesquisa - Souza, Mauren Mata de (2015)
The objective of the presente work is to investigate how academic audiovisual articles of research protocol (AAARPs) are organized in terms of the visual semiotic mode and the verbal semiotic mode. To accomplish this, we used the theoretical-methodological framework of Critical Genre Analysis (CGA). The analysis of the visual semiotic mode was carried out using the categories of the representational metafunction of the Grammar of Visual Design (KRESS; van LEEUWEN, 2006) and the analysis of the verbal semiotic mode was carried out using the categories of the ideational metafunction of the Systemic-Functional Grammar (HALLIDAY, 2004). The corpus of this research consists of 10 AAARPs, five from the Biology field and five from the Medicine field, published in JoVE between 2011 and 2015 and with free access. The transcription of the oral verbal language present in the corpus, after the transcription, the clauses were parced. The visual semiotic mode was divided in shots, defined by the movement of the camera without cuts or editions (IEDEMA, 2001), so the shots did not have a fixed time interval. The clauses and shots were analyzed according to the categories of the ideational and representational metafunctions, respectively. Through the patterns found in the analysis of the two semiotic modes, we tried to identify a rhetorical organization in the AAARPs. The results showed a predominance of material processes (75,7%) in the verbal semiotic mode and of the narrative structure of transactional action (62,7%) in the visual semiotic mode, what suggests an emphasis in action, in the protocol itself. It was possible to identify four sections in the AAARPs: Rationale, Protocol, Representative Results and Conclusion. In the Rationale section, there is predominance of relational processes in the main clauses and of verbal narrative structure, showing the researcher speaking. In the Protocol section, there is predominance of material processes and of narrative structure of transactional action. In the Representative Results section, there is predominance of material and relational processes and of the conceptual analytic structure. In the Conclusion section, there is predominance of relational processes in the main clauses and of verbal narrative structure, showing the researcher speaking. The overall predominance of material processes and great occurrence of circumstances of location in time indicating sequence, together with the emphasis in the Protocol section, suggests an instructional character of the AAARPs. In the proposal of the umbrella project in which this research is inserted, we hope that the results presented here can contribute to the promotion of multiliteracies (COPE; KALANTIZIS, 2000) and also serve as base to other invetigations of academic or multimodal genres using the CGA framework.